DOI: 10.17077/etd.lwm4nglx
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing cartilage-specific T1rho MRI for clinical translation and application

Abstract: showing concentric-ringed, carrageenan-agarose phantom used in this work. The midline 20 ms T1rho images for the 1.5T and 3.0T scans are shown at right.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
(186 reference statements)
0
4
0
Order By: Relevance
“…34 While T1rho is sensitive to both T1 and T2 tissue properties, the biochemical basis for T1rho relaxation in cartilage at clinical field strengths and typical clinical spin lock frequencies are not fully understood due to differences in relaxation processes between higher and lower fields and spin lock frequencies. 35,36 Studies consistently show the sensitivity of compositional MRI to potentially reversible cartilage matrix changes. Several studies have shown reductions in T2 and T1rho values after running, a repetitive load-bearing activity [37][38][39] demonstrating the sensitivity of these metrics to transient changes in cartilage water content and collagen orientation.…”
Section: Compositional Mri Allows For Noninvasive Early Assessment Of Articular Cartilage Statusmentioning
confidence: 96%
See 1 more Smart Citation
“…34 While T1rho is sensitive to both T1 and T2 tissue properties, the biochemical basis for T1rho relaxation in cartilage at clinical field strengths and typical clinical spin lock frequencies are not fully understood due to differences in relaxation processes between higher and lower fields and spin lock frequencies. 35,36 Studies consistently show the sensitivity of compositional MRI to potentially reversible cartilage matrix changes. Several studies have shown reductions in T2 and T1rho values after running, a repetitive load-bearing activity [37][38][39] demonstrating the sensitivity of these metrics to transient changes in cartilage water content and collagen orientation.…”
Section: Compositional Mri Allows For Noninvasive Early Assessment Of Articular Cartilage Statusmentioning
confidence: 96%
“…T1rho measures a combination of T1 (spin‐lattice) and T2 (spin‐spin) relaxations 34 . While T1rho is sensitive to both T1 and T2 tissue properties, the biochemical basis for T1rho relaxation in cartilage at clinical field strengths and typical clinical spin lock frequencies are not fully understood due to differences in relaxation processes between higher and lower fields and spin lock frequencies 35,36 …”
Section: Compositional Mri Allows For Noninvasive Early Assessment Of Articular Cartilage Statusmentioning
confidence: 99%
“…Previous work both at this and other institutions has demonstrated the capacity of MRI to noninvasively identify morphometric and compositional features of traumatic injury and possible markers of progressive disease. [102,109] That previous work has also demonstrated the extensibility of imaging-derived measures from a research setting into a clinical setting. [109] However, that previous work has not fully explored the use of MRI diagnostic techniques to evaluate the entire history of disease from traumatic onset through PTOA progression to establish efficacy in a translatable preclinical model.…”
Section: Resultsmentioning
confidence: 96%
“…[102,109] That previous work has also demonstrated the extensibility of imaging-derived measures from a research setting into a clinical setting. [109] However, that previous work has not fully explored the use of MRI diagnostic techniques to evaluate the entire history of disease from traumatic onset through PTOA progression to establish efficacy in a translatable preclinical model. The purpose of the present work was to model acute cartilage injury, and correlate imaging findings to end-stage osteoarthritic changes.…”
Section: Resultsmentioning
confidence: 96%